The City of Beach Turism Becomes a City of Alert and Responsive First Aid for Drowning Victims Along The Coast di Kelurahan Pasir Kecamatan Pariaman Tengah Kota Pariaman - Asman, Aulia; Sari, Reska Handayani; Ramaita; Abdul Malik; Alimuddin (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2025)
Kelurahan Pasir has the widest beach tourism and the densest coastal community. Fast and responsive first aid for drowning victims in coastal communities is very important because the risk of drowning often occurs. Drowning is an emergency that requires speed and responsiveness of first aid. The impact of delayed first aid for drowning victims is death. Drowning is the 3rd leading cause of death in unintentional injuries. In 2021, there were 3 cases of drowning victims. The results of observations and interviews with coastal communities and fishermen, said they did not know and did not understand how to first aid drowning victims. So it is necessary to carry out education, training in coaching the coastal community in Pasir Village in the form of simulating the first aid for drowning victims, creating a SIGAP (alert and responsive) drowning nagari group and using the techno first aids application. The activity aims to assist government programs in building and increasing the independence of coastal communities to become safe, comfortable, safe tourist areas, and able to provide first aid for drowning victims. The service was carried out for 3 years based on the following partner problems in Pasir Village: Improving the understanding and skills of the Pasir Village Coastal Community about first aid for drowning victims which is still low.